The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2005
DOI: 10.1097/00008390-200508000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of candidate genes through a proteomics-based approach in primary cell lines from malignant melanomas and their metastases

Abstract: Proteomics provides a powerful approach for screening alterations in protein expression and post-translational modification associated with particular human diseases. In this study, the analysis of protein expression was focused on malignant melanoma in order to determine the candidate genes involved in tumour progression. The proteomes of cultured melanocytes and of cell lines from primary and metastatic lesions of one malignant melanoma patient were profiled using two-dimensional electrophoresis (2-DE) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Although Prx II is a 2-Cys thioredoxin peroxidase and a cellular antioxidant, it interacts with activated PDGF receptor h, unlike other peroxiredoxins, and suppresses its phosphorylation (19). Down-regulation of Prx II was recently shown to be associated with progression of melanomas (20) and urinary bladder cancers (21). Molecular mechanisms for the down-regulation have been unknown, but our study here showed that gene silencing by promoter methylation is one of the mechanisms.…”
Section: Discussionmentioning
confidence: 60%
“…Although Prx II is a 2-Cys thioredoxin peroxidase and a cellular antioxidant, it interacts with activated PDGF receptor h, unlike other peroxiredoxins, and suppresses its phosphorylation (19). Down-regulation of Prx II was recently shown to be associated with progression of melanomas (20) and urinary bladder cancers (21). Molecular mechanisms for the down-regulation have been unknown, but our study here showed that gene silencing by promoter methylation is one of the mechanisms.…”
Section: Discussionmentioning
confidence: 60%
“…Among these enzymes, Prx is the most abundant enzyme and is known to be involved in receptor tyrosine kinase-mediated signal transduction (12). Interestingly, it has recently been shown that one of the Prx family members Prx2 (gene loci, PRDX2), which belongs to 2-cys Prx subfamily and reduces the peroxides in the presence of NADPH by coupling with thioredoxin/thioredoxin reductase system, is downregulated in melanoma cell lines and particularly in metastatic malignant types (13,14). However, the function of the Prx2 enzyme in the melanoma cell growth and metastasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the proteins that were found to be more abundant in tumor samples were stress response proteins, including multiple heat shock proteins. 111 A similar study demonstrated high levels of hepatocytederived growth factor levels in tumor samples. 112 In an effort to examine the mechanism of the antitumor effect of interferon alfa, the proteomes of two melanoma cell lines, one interferon-sensitive, the other interferon-resistant, were compared by use of 2D electrophoresis and mass spectroscopy.…”
Section: Cutaneous Oncology-melanomamentioning
confidence: 81%